Problematika Evaluasi Pembelajaran Bahasa Arab Berbasis Digital - Nawal Sa’adah; Wilda Widya Armadani; Muhammad Kholilurrahman; Andi Nur Pratiwi; Ummul Khaeriah; Herdah Herdah (Pusat Riset dan Inovasi Nasional, 2026)
This study examines the problematics of digital-based evaluation in Arabic language learning in the context of contemporary educational transformation. The background of this research is rooted in the increasing use of digital technology in assessment practices, which raises questions regarding its effectiveness in measuring comprehensive language competence. The objective of this study is to analyze the main challenges faced in implementing digital evaluation in Arabic language learning. This research employs a qualitative approach through library research, utilizing documentation techniques to collect data from relevant scholarly sources published between 2020 and 2026. The data were analyzed using content analysis by identifying, categorizing, and interpreting recurring issues in digital assessment practices. The findings indicate that digital evaluation still faces several limitations, including the inability to measure productive language skills comprehensively, issues of validity and reliability, potential academic dishonesty, low digital literacy among users, unequal access to technology, suboptimal evaluation design, ethical concerns in technology use, and lack of alignment with the communicative nature of Arabic language learning. These findings imply that digital evaluation requires an integrative approach that combines technological innovation with pedagogical principles, emphasizing authentic and performance-based assessment. The study also highlights the importance of improving digital literacy and providing adequate infrastructure to ensure fair and effective evaluation practices.